Pro-Cons Analysis of the Policy of Indonesian Capital Movement Policy in The Era of The Covid-19 Pandemic - Ageng Nugroho Baniargi; Endang Larasati; Tri Yuniningsih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The discourse of moving the country's capital city to the 'Nusantara' has drawn various polemics among the public. Especially in the midst of the ongoing COVID-19 pandemic. The purpose of this study is to find out the pros and cons of the polemic of the policy of moving the country's capital city in the era of the covid-19 pandemic. The research method used is a descriptive qualitative approach with data sources in the form of secondary data. The results of this study are that those who are pro argue that moving the capital city should be carried out immediately considering that Jakarta is no longer ideal as the capital city of Indonesia and it is time for equity to occur in Indonesia. Meanwhile, the contra considers environmental aspects and also consider the pandemic as a problem that must be focused on first. Therefore, the government should be able to consider this policy carefully.